2014
DOI: 10.1176/appi.ajp.2013.13070966
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Dysregulation in Attention Deficit Hyperactivity Disorder

Abstract: It has long been recognized that many individuals with ADHD also have difficulties with emotion regulation but lack of consensus on how to conceptualize this clinically challenging domain renders a review timely. The authors examine the current literature using both quantitative and qualitative methods. Three key findings emerge. First, emotion dysregulation is prevalent in ADHD throughout the lifespan and is a major contributor to impairment. Second, emotion dysregulation in ADHD may arise from deficits in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

57
678
3
23

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 892 publications
(761 citation statements)
references
References 152 publications
57
678
3
23
Order By: Relevance
“…Although no longer diagnostic, impaired emotion regulation is common amongst individuals with ADHD throughout the lifespan (Shaw, Stringaris, Nigg, & Leibenluft, 2014) -and believed to be an important element in functional impairment in daily life (e.g., Anastopoulos et al, 2011). Recently, there is a renewed interest in emotion regulation in ADHD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no longer diagnostic, impaired emotion regulation is common amongst individuals with ADHD throughout the lifespan (Shaw, Stringaris, Nigg, & Leibenluft, 2014) -and believed to be an important element in functional impairment in daily life (e.g., Anastopoulos et al, 2011). Recently, there is a renewed interest in emotion regulation in ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is a renewed interest in emotion regulation in ADHD. In their review, Shaw et al (2014) defined emotional dysregulation as excessive and inappropriate emotional reactions with regard to social norms; emotional lability characterized by rapid mood shifts; and disrupted allocation of attention to emotional stimuli. They concluded that some form of emotional dysregulation is present in 25%-45% of children and 30%-70% of adults with ADHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…감각처리에 문제가 있는 자폐스펙트럼 장애(Autism Spectrum Disorder: ASD)나 주의력결핍과잉행동장애 (Attention Deficit Hyperactivity Disorder: ADHD) 아동에서 감정조절 장애는 일반적이라고 인식되어 오고 있다 (Shaw, Stringaris, Nigg, & Leibenluft, 2014).…”
unclassified
“…감정조절의 어려움은 ASD나 ADHD 아동의 주요 문제점 은 아니지만 부모와 임상가들에게 오랫동안 강조되어 온 문제점이다 (Geller, 2005;Shaw et al, 2014). 특히, ASD 아동은 사회성과 적응기술의 부족, 부정적 감정, 불 안과 높은 연관성을 보인다 (Ben-Sasson et al, 2008;Liss, 2006;Pfeiffer, Kinnealey, Reed, & Herzberg, 2005).…”
unclassified